Genetic diversity of pepper genotypes for use as ornamental plants - da Silva Guimarães, Maria Eduarda; Freire, Ana Izabella; de Oliveira, Ana Carolina Ribeiro; Pereira, Ariana Mota; Gonçalves, Dreice Nascimento; Finger, Fernando Luiz (Comunicata Scientiae, 2021)
The commercialization of ornamental pepper trees constitutes an important source of income for the agricultural populations. Despite the great variability that exists, in Brazil few commercial varieties are used for this purpose. The presence of genetic diversity is the main criterion for a successful selection and progress in a breeding program. The objective of this study was to quantify the genetic diversity among pepper genotypes, aiming at their use in ornamentation, through the description of morpho-agronomic characteristics. 14 quantitative characteristics and seven qualitative characteristics related to plant, flower and fruit were evaluated in 29 pepper (Capsicum annuum) genotypes. Using the mixed model methodology and analysis of genetic diversity, genetic variability was verified between the genotypes. The genotypes were divided into seven groups of genetic similarity in terms of quantitative characteristics, three in terms of qualitative characteristics and five groups considering the characteristics together. Thus, the genetic variability of the genotypes can be exploited to produce superior combinations while.